Patterns of change in the justifiability of euthanasia across OECD countries - Tormos, Raül; Rudnev, Maksim; Bartolomé Peral, Edurne (Frontiers in Political Science, 2023)
The justifiability of euthanasia among the public has increased as more countries adopted the laws permitting a range of the end-of-life practices. However, there is a dearth of longitudinal and comparative studies investigating attitudes toward euthanasia. As a result, it is unclear whether the rise in justifiability indicates a period-specific trend or generational change. We used data from the European and World Values Survey spanning from 1981 to 2021 to investigate period variations, between-cohort differences, and within-cohort changes across 35 affluent countries. Our descriptive results supported our hypotheses, indicating an increase in the justifiability of euthanasia in virtually all countries, with both overall changes and changes within each cohort occurring toward higher degrees of justifiability. In addition, newer periods and younger cohorts were found to be more permissive than their older counterparts. We verified these consistent increases in the justifiability of euthanasia using dynamic comparative multilevel regression and a comparative version of the cross-classified random effects regressions. Our results were in line with modernization theory, as we observed a gradual change in attitudes between cohorts due to generational replacement. However, we also identified intra-cohort changes related to the processes of human development across countries. Although some of the robustness checks produced ambiguous results in separating period and cohort effects, the combination of the latter three components aligns with substantive theory. Our findings indicate a more complex pattern of change than predicted by the leading approach in political socialization research, namely the impressionable years model.